Effects of dried plum mixtures on total aerobic growth in uncooked ground beef - L.K. Thompson; Daniel Y.C. Fung (Kansas Agricultural Experiment Station Research Reports, 2003)
Spices and plant components are being used more often in food products as natural antimicrobials. Dried plums are effective antimicrobials against foodborne pathogens including Escherichia coli O157:H7. The objective of this experiment was to determine the ability of dried plum mixtures to increase the shelf life of ground beef at refrigeration temperatures. Ground beef (80% lean) was mixed with 6% dried plum mixtures and stored at 45°F. Ground meat containing any of the seven dried plum mixtures remained at the initial total aerobic count of 6 log CFU/gram after 13 days compared to 8.5 log CFU/gram at 13 days for controls (without dried plum).
Keywords: Cattlemen' s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Dried plum mixtures; Aerobic growth; Uncooked ground beef